(untitled) (Paliativní medicína, 2023)
It is only natural for an occupational therapist to focus on the meaningful activity of an individual and to include caregivers in their interventions. Occupational therapy often uses a person-centered approach, therefore tries to map the wishes of an individual and also with the help of various tools, support the performance of those activities that are important. Therefore, occupational therapists should be full-fledged members of palliative teams. A questionnaire survey was conducted, where it was explored what roles and competencies an occupational therapist should be and what areas occupational therapists focus on in palliative care. The results suggest that occupational therapists have their role, either in psychological, physical, spiritual, or social support of the given person and his family, as well as in recommending various technical aids and alleviating pain, and using fatigue-saving strategies or approaches. Occupational therapists in palliative care should be empathetic, humane, resilient, accommodating, respectful, patient, willing to work in a team, and should be able to communicate well.